Artistic Integrity’ in the English translation of Abdelatif Laabi’s novel Le fond de la jarre - Khalid Majhad (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2018)
The translation of literature has often been discussed and critiqued in terms of one core ideological question of cultural representation, namely in matters of exclusionary selection of certain texts or authors for translation and the discursive manipulation that goes with it. In this study, as the title suggests, the translation of the francophone Maghrebi novel into English is assessed on the basis of its faithfulness to the artistic spirit of the original text and to the distinctiveness of its author. This paper is mainly about ethics and esthetics in postcolonial literary translation and treats questions of rigour and faithfulness in emphasizing the aesthetic potential of postcolonial literatures and in showing the individualism of each author, besides mere extraction of ethnographic knowledge. Artisitc integrity, implying both completeness and principled professional practice, is measured according to a framework developed by Chinese translation scholar Jin Di (2003) and a related one by Boase-Beier (2010) on the application of cognitive stylistics to translation assessment. Faithful style reproduction in the target text is taken here to be the principal indicator of translational artistic integrity since style is the element that captures the ‘spirit’ and literariness of the literary work. Ignoring it is a form of injustice and a sign of sloppiness in dealing with minor literatures from the ‘Third World’. The paper assesses the English translation of Le fond de la jarre by Moroccan author Abdelatif Laabi.